Impact of Tenascin-C on Radiotherapy in a Novel Syngeneic Oral Squamous Cell Carcinoma Model With Spontaneous Dissemination to the Lymph Nodes - Spenlé, Caroline; Loustau, Thomas; Burckel, Hélène; Riegel, Gilles; Abou Faycal, Chérine; Li, Chengbei; Yilmaz, Alev; Petti, Luciana; Steinbach, Fanny; Ahowesso, Constance; Jost, Camille; Paul, Nicodème; et al. (Frontiers in Immunology, 2021)
Radiotherapy, the most frequent treatment of oral squamous cell carcinomas (OSCC) besides surgery is employed to kill tumor cells but, radiotherapy may also promote tumor relapse where the immune-suppressive tumor microenvironment (TME) could be instrumental. We established a novel syngeneic grafting model from a carcinogen-induced tongue tumor, OSCC13, to address the impact of radiotherapy on OSCC. This model revealed similarities with human OSCC, recapitulating carcinogen-induced mutations found in smoking associated human tongue tumors, abundant tumor infiltrating leukocytes (TIL) and, spontaneous tumor cell dissemination to the local lymph nodes. Cultured OSCC13 cells and OSCC13-derived tongue tumors were sensitive to irradiation. At the chosen dose of 2 Gy mimicking treatment of human OSCC patients not all tumor cells were killed allowing to investigate effects on the TME. By investigating expression of the extracellular matrix molecule tenascin-C (TNC), an indicator of an immune suppressive TME, we observed high local TNC expression and TIL infiltration in the irradiated tumors. In a TNC knockout host the TME appeared less immune suppressive with a tendency towards more tumor regression than in WT conditions. Altogether, our novel syngeneic tongue OSCC grafting model, sharing important features with the human OSCC disease could be relevant for future anti-cancer targeting of OSCC by radiotherapy and other therapeutic approaches.